Anxiety and depression among infertile women: a cross-sectional survey from Hungary - Enikő Lakatos; Judit F Szigeti; Péter P Ujma; Réka Sexty; Piroska Balog (BMC, 2017)
Abstract Background Infertility is often associated with a chronic state of stress which may manifest itself in anxiety-related and depressive symptoms. The aim of our study is to assess the psychological state of women with and without fertility problems, and to investigate the background factors of anxiety-related and depressive symptoms in women struggling with infertility. Methods Our study was conducted with the participation of 225 (134 primary infertile and 91 fertile) women, recruited in a clinical setting and online. We used the following questionnaires: Spielberger Trait Anxiety Inventory (STAI-T), Shortened Beck Depression Inventory (BDI) and Fertility Problem Inventory (FPI). We also interviewed our subjects on the presence of other sources of stress (the quality of the relationship with their mother, financial and illness-related stress), and we described sociodemographic and fertility-specific characteristics. We tested our hypotheses using independent-samples t-tests (M ± SD) and multiple linear regression modelling (ß). Results Infertile women were younger (33.30 ± 4.85 vs. 35.74 ± 5.73, p = .001), but had significantly worse psychological well-being (BDI = 14.94 ± 12.90 vs. 8.95 ± 10.49, p < .0001; STAI-T = 48.76 ± 10.96 vs. 41.18 ± 11.26, p < .0001) than fertile subjects. Depressive symptoms and anxiety in infertile women were associated with age, social concern, sexual concern and maternal relationship stress. Trait anxiety was also associated with financial stress. Our model was able to account for 58% of the variance of depressive symptoms and 62% of the variance of trait anxiety. Conclusions Depressive and anxiety-related symptoms of infertile women are more prominent than those of fertile females. The measurement of these indicators and the mitigation of underlying distress by adequate psychosocial interventions should be encouraged.